Symposium 2: Critical TEL: The importance of theory and theorisation - Sclater, Madeleine; Lally, Vic (Proceedings of the International Conference on Networked Learning, 2016)
This paper explores the role of theory in Technology Enhanced Learning, and the research community. We consider Cultural Historical Activity Theory (CHAT) as an example, but we strongly feel that our argument has broader application to the use of theory as part of the intellectual ‘self-defence toolkit’ that researchers and practitioners in the critical TEL community need to consider if they are to ‘resist’ the crises arising from educational globalisation. Theory can offer us the language, history, scope, and power that we need to be reflexively aware of both our own interests and those of others who are actors in the settings in which we are working.